Information management process in dairy livestock activity - Dos Santos, Carlos Eduardo Moreno [UNESP]; Machado, João Guilherme de Camargo Ferraz [UNESP]; Satolo, Eduardo Guilherme [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2020)
Milk producer needs to continuously monitor market occurrences and the technological innovations that emerge, adopting a business posture and adjusting to new market rules, emphasizing the importance of adopting tools to manage information. Thus, the aim of the article was to diagnose the application of information management processes by milk producers in the Tupa-SP region. For this, an exploratory, qualitative research was carried out, using the multiple case technique and promoting data triangulation, through interviews, on-site observation and verification of documents related to milk production. The sample consisted of milk producers in the Tupa-SP region, selected from a database of the former Alta Paulista Dairy Cooperative (COPLAP). The results indicated that the use of information technologies in the management of technical and managerial information, respectively, is incipient or nonexistent. The phases of the information management process carried out by the interviewed producers include the identification of the need, the search and the use of the information, are conducted with low frequency and preferably by informal sources. This creates difficulties in organizing and recording information, with regard to the origin and its application, and, consequently, its recovery for future uses.
El proceso de gestión de la información en la actividad ganadera láctea
O processo de gestão da informação na atividade pecuária leiteira
Keywords: Agribusiness; Dairy farming; Farmers; Information management; Technical and managerial information